2022
DOI: 10.1038/s41422-022-00630-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticle-encapsulated mRNA antibody provides long-term protection against SARS-CoV-2 in mice and hamsters

Abstract: Monoclonal antibodies represent important weapons in our arsenal to against the COVID-19 pandemic. However, this potential is severely limited by the time-consuming process of developing effective antibodies and the relative high cost of manufacturing. Herein, we present a rapid and cost-effective lipid nanoparticle (LNP) encapsulated-mRNA platform for in vivo delivery of SARS-CoV-2 neutralization antibodies. Two mRNAs encoding the light and heavy chains of a potent SARS-CoV-2 neutralizing antibody HB27, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Importantly, in vivo study suggested that intravenous administration of mRNA-HB 27 - LNPs in mice model showed improved circulating half-life with longer protection for 1,7 and even 63 days against SARS-CoV-2, irrespective to free HB 27 antibody. Additionally, study further revealed that the antiviral efficacy of mRNA-HB 27 - LNPs in the hamster model was observed to be dose-dependent manner after prophylactic administration [155] .…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, in vivo study suggested that intravenous administration of mRNA-HB 27 - LNPs in mice model showed improved circulating half-life with longer protection for 1,7 and even 63 days against SARS-CoV-2, irrespective to free HB 27 antibody. Additionally, study further revealed that the antiviral efficacy of mRNA-HB 27 - LNPs in the hamster model was observed to be dose-dependent manner after prophylactic administration [155] .…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 90%
“… [154] Deng et al, mRNA incorporated lipid NPs (mRNA- HB 27 -LNPs Antiviral efficacy against corona virus In- vivo study speculated the improved circulating half-life with greater protection against virus after i.v administration of mRNA-HB 27 -LNPs into mice model. [155] Sanna et al, Remdesivir loaded targeted NPs (RDV-TNP-1 Antiviral activity against COVID 19 RDV-TNP-1 showed highest binding propensity to ACE2 receptor with enhanced antiviral efficacy and better biocompatibility. [156] Zheng et al, RBC hitchhiked ivermectin loaded PLGA NPs (RBC-IVM-PNPs and chitosan coated PLGA NPs (RBC-IVM-CSPNPs) Anti-inflammatory activity of ivermectin associated with SARS-CoV 2 virus.…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 99%
“…Third, serum titres of anti-SARS-CoV-2 antibodies decrease over time 52 , and RBD-targeted antibodies may protect for only a few months 46 . Broadly neutralizing super-antibodies 53 and antibodies encoded via lipid-nanoparticle-encapsulated mRNA 54 may have the potential to provide longer-term protection against variants of concern. Lastly, the need for intravenous or intramuscular infusion of neutralizing antibodies, their strict storage and distribution requirements, and high production costs are important factors that limit the accessibility of neutralizing antibodies to patients living in resource-limited regions with poor medical facilities.…”
Section: Viral Targets For Antiviral Agentsmentioning
confidence: 99%
“…In addition to the Chikungunya virus vaccine, preclinical trials of mRNA vaccines encoding the corresponding antibodies have been completed in other viruses such as the Influenza A virus vaccine, SARS-CoV-2 vaccine ZIKV, Respiratory Syncytial Virus (RSV), and Human metapneumovirus (hMPV) which have obtained promising results [125][126][127][128].…”
Section: Chikungunya Virus Vaccinementioning
confidence: 99%